2020
DOI: 10.1109/access.2020.2982401
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Classification of Attention Deficit Hyperactivity Disorder With l 2,1-Norm Linear Discriminant Analysis and Binary Hypothesis Testing

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a high incidence of neurobehavioral disease in school-age children. Its neurobiological diagnosis (or classification) is meaningful for clinicians to give proper treatment for ADHD patients. The existing ADHD classification methods suffer from two problems, i.e., insufficient data and noise disturbance. In this paper, a high-accuracy classification method is proposed by using brain Functional Connectivity (FC) as ADHD features, where an l 2,1-norm Linear Discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…We employed several state-of-the-art approaches for comparison, including ML-based methods such as R-Relief [6], L 1 BioSVM [9], and Fusion fMRI [40], as well as DL-based methods consisting of Deep fMRI [18], AAEN ( [21], CDAE [22], DVAE [24], and STAAE [25]. In addition, we introduced some methods under the BHT framework for comparison, namely SP-BH [29] and SP-l 2,1 -BH [28]. These methods utilize subspace learning and l 2,1 -norm subspace learning, respectively, for ADHD classification.…”
Section: Classification Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed several state-of-the-art approaches for comparison, including ML-based methods such as R-Relief [6], L 1 BioSVM [9], and Fusion fMRI [40], as well as DL-based methods consisting of Deep fMRI [18], AAEN ( [21], CDAE [22], DVAE [24], and STAAE [25]. In addition, we introduced some methods under the BHT framework for comparison, namely SP-BH [29] and SP-l 2,1 -BH [28]. These methods utilize subspace learning and l 2,1 -norm subspace learning, respectively, for ADHD classification.…”
Section: Classification Comparison With Other Methodsmentioning
confidence: 99%
“…Notably, a modified AE network (AENet) [26,27] also demonstrated attractive performance. When integrated into an existing binary hypothesis testing (BHT) framework [28,29], AENet achieved an accuracy of 99.7%. However, it is observed that most of the aforementioned methods were evaluated on single datasets, resulting in varying features for ADHD on multiple datasets alongside inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the use of decision trees to analyse clinical data [11], [12]. Using the tree and its principles to forecast on a dataset is the heart of this method.…”
Section: -Decision Treementioning
confidence: 99%
“…e basic idea of linear discriminant analysis (LDA) is to project high-dimensional data samples into the optimal discriminant vector space, which is used to separate two or more categories of objects or events and find the most appropriate projection space so that the data samples with multiple categories of features can project on this space with the least intersection to have the best separation effect [11].…”
Section: Linear Discriminant Analysismentioning
confidence: 99%